A modified electrode for the electrochemical reduction of isoflurane. - Compton, R; Northing, R; Fleet, G; Son, J; Bashyal, B (1988)
The popular anaesthetic gas isoflurane is found to be electrochemically inert on a wide range of conventional electrode materials in both aqueous and non-aqueous solvents. However the chemically modified electrode produced by depositing the novel electroactive polymer, poly(vinylfluoranthene), onto a platinum electrode is shown to mediate electron transfer to the anaesthetic thus bringing about its electro-reduction and so offers the promise of amperometric electrochemical sensors based on this electrode.